Debriefing for the Transfer of Learning: The Importance of Context. (June 2019) - Rivière, Etienne; Jaffrelot, Morgan; Jouquan, Jean; Chiniara, Gilles
Abstract : The advent of simulation-based education has caused a renewed interest in feedback and debriefing. However, little attention has been given to the issue of transfer of learning from the simulation environment to real-life and novel situations. In this article, the authors discuss the importance of context in learning, based on the frameworks of analogical transfer and situated cognition, and the limitations that context imposes on transfer. They suggest debriefing strategies to improve transfer of learning: positioning the lived situation within its family of situations and implementing the metacognitive strategies of contextualizing, decontextualizing, and recontextualizing. In contextualization, the learners' actions, cognitive processes, and frames of reference are discussed within the context of the lived experience, and their mental representation of the situation and context is explored. In decontextualization, the underlying abstract principles are extracted without reference to the situation, and in recontextualization, those principles are adapted and applied to new situations and to the real-life counterpart. This requires that the surface and deep features that characterize the lived situation be previously compared and contrasted with those of the same situation with hypothetical scenarios ("what if"), of new situations within the same family of situations, of the prototype situation, and of real-life situations. These strategies are integrated into a cyclical contextualization, decontextualization, and recontextualization model to enhance debriefing.